Pengaruh Kualitas Layanan Akademik Terhadap Loyalitas Mahasiswa - Zulfa, Eva; Ramdani, Agus; Baehaqi, Baehaqi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
A good university needs to be balanced with good quality academic services. This study aims to determine the effect of academic service quality (X) on Student Loyalty (Y). This study is an ex-post facto study with 40 student respondents as a sample determined based on purposive sampling technique in determining the sample. The instrument used in this study was a questionnaire with a Likert scale. Linear regression is used to test the hypothesis of the strength of the influence between the independent variables and the dependent variable. The results showed that there was an effect of academic service quality (X) on student loyalty (Y) by 50.0%. These findings indicate that: the quality of academic services (X) has an influence on student loyalty (Y).